Perolehan dan Hak Waris dari Istri Kedua, Ketiga dan Keempat dalam Hukum Kewarisan Islam di Indonesia : (Sebuah Pemahaman dengan Ilmu Hukum, Filsafat Hukum dan Paradigmatik) - Arif Bijaksana (Jurnal Manajemen dan Pendidikan Agama Islam, 2023)
In Islamic inheritance law, it is a law derived from the Qur'an where the truth of the teachings or theories is absolutely true because it is a revelation from God. Islamic inheritance law in general theory is a law conveyed by Allah SWT to the Prophet Muhammad SAW to be applied and made law by mankind. In legal philosophy it is said that the law is for humans, in Islam the Islamic inheritance law is absolute because it has been regulated in it. Problems arise in its application in society, especially in terms of the rights and acquisition of the second wife, third wife and fourth wife. There is discrimination in the distribution of inheritance that violates existing rules and provisions and there is a mental attitude that does not or is reluctant to carry out and follow the provisions of Islamic inheritance law regarding the acquisition and inheritance rights of the second wife, third wife or fourth wife.